Pengenalan Teknologi Pertanian Berkelanjutan Kepada Petani Di Lahan Kering Desa Gumantar, Kabupaten Lombok Utara - I Komang Damar Jaya; Bambang Budi Santoso; Jayaputra Jayaputra (Jurnal Gema Ngabdi, 2021)
The main obstacle faced in the development of seasonal crops on dryland is the availability of water and low soil fertility. As a result, the cropping index (IP) of dryland is very low because crops are grown in the rainy season only. The use of inorganic fertilizers is also very high in order to obtain adequate crop yields. Such practices can result in a reduction in the organic carbon content in the soil in the long term. Soil fertility can be maintained if the soil contains a lot of organic carbon. Organic carbon in the soil can increase soil fertility by preventing nutrient loss, increasing soil physical stability, increasing the soil's ability to retain water and increasing the consortium of microorganisms. An introduction of sustainable agriculture technology was carried out to provide understanding to farmers in the dryland of Gumantar Village, North Lombok Regency (KLU) about the importance of sustainable agriculture in order to maintain soil fertility and land productivity. The activity was carried out by making a demonstration plot of aerobic composting of mungbean waste and then followed by an in-situ test of the benefits of compost for chili plants. As a comparison, plots were made for planting chili plants without compost treatment. Aerobic composting was done by using BeKa decomposer (PT. Indo Acidatama Tbk). Several formal and informal meetings were held with farmers to increase their understanding of sustainable agriculture. The results of the activities indicated that the target farmers did not understand at all about sustainable agriculture. The good news was that the farmers passionate about understanding the benefits of sustainable agriculture. At the end, the participants understanding and beliefs about sustainable agriculture improved after seeing the yields of chili plants in the compost treatment which were much higher than those without compost treatment.